(3TQM GdebOeI GdCLQhejIs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3eMeO Hf GdTjN CMeO Hf MHjH GdQMHjs)
(3ChdgG (B:s
(3fGbU GdChd, hjHJOC YfO bhdg(B: (3RjO bGe hGdNGeS GSe cGf hGSe CNhGJgG fMh cGf RjO bGFeG hGdSGOS NHQ Ef hNHQ CNhGJgG fMh Ef RjOG bGFes
(3BNQgG (B:s
(3heG CTHg Pdc ef CeKdI GdbSejf GdChdjf Ch GdKdGKI hCeG JGHY GdeNahV abO JbOe PcQg aj GdeQahYGJ adjQGLY LejY Pdcs
(3aQZ GdeDda ef JCdja GdcJGH HYO YUQ GdLeYI Chd jhe ef TQM QLH SfI (B887(3g` , hgj fSNI efbhdI Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 297s
(3eYLe GdeDdajf(B: 8 / 26s
(3cTa GdXfhf(B: 2 / 1796s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs